The Research Evolution of Financial Performance, Customer Trust, and Customer Loyalty in Sharia Banking Sector: a Bibliometric Analysis - Bachtiar Wijaya; Budi Eko Soetjipto; Madziatul Churiyah (Economics and Business Journal (ECBIS), 2026)
The transformation of the Islamic banking industry requires the integration of financial performance, customer trust, and customer loyalty as the foundation for institutional sustainability. This study aims to map the intellectual evolution of this field of study and identify dominant themes, development trends, and opportunities for research gaps in the international literature. The method employed is a bibliometric analysis based on a Systematic Literature Review (SLR) using the PRISMA procedure on Scopus articles from 2018 to 2025. From a selection process of 2,009 documents, the study identified 37 articles meeting the inclusion criteria, which were then analyzed using co-authorship, co-occurrence, network, overlay, and density visualizations. The results indicate that the themes of customer loyalty, service quality, customer satisfaction, and customer trust form the core of the intellectual structure with the highest connectivity, while the themes of financial performance, digital trust, banking mergers, and Sharia banking mergers remain in low-density areas, signaling opportunities for research development. The novelty map also reveals a shift in focus from traditional loyalty models toward digital banking, customer experience, and e-CRM. The novelty of this study lies in its proposal of a new research agenda model that integrates financial performance–customer trust–customer loyalty within the context of digital transformation and the consolidation of Sharia banks. Thus, it is hoped that this study can provide a conceptual foundation for future cross-national empirical research